Pengaruh Kepuasan dan Nilai yang Dipersepsikan Nasabah terhadap Minat Menggunakan Baitul Maal Wa Tamwil (BMT) dalam Persepsi Masyarakat - Yusril Ihza Mahendra; Slamet Asih Muliya; Dwi Fatmawati (An-Nisbah: Jurnal Perbankan Syariah, 2021)
Influence is a power that arises or arises from something (person or thing) which contributes to a person's character, belief, or action. Satisfaction is defined as a person's feeling of satisfaction that arises after using a product or enjoying a company's services which then compares the perception to the performance of a product and its expectations. The effect of one's satisfaction on a product or service will deliver value that someone will perceive in the form of being willing to buy or use the goods and services offered. Meanwhile, Baitul Maal Wa Tamwil (BMT) is a microfinance institution that operates using sharia principles.